Kinerja Badan Pengawas Pemilihan Umum (Bawaslu) Kota Tanjungpinang Dalam Pengawasan Pada Pemilihan Tahun 2024 - SRI AMBAR RINAH; Agus Abdullah; Diah Siti Utari; Endri Sanopaka; Fitri Dewi Wulandari; Neng Suryanti Nengsih (STISIPOL Raja Haji, 2026)
This study was motivated by the fact that the 2024 elections in Tanjungpinang City were conducted without any findings or reports of alleged violations during the election process. This situation is an interesting phenomenon to analyze because Tanjungpinang City is classified as a high-risk area based on the 2024 Regional Election Vulnerability Index (IKP). This situation does not directly indicate the absence of potential violations; rather, it must be analyzed from the perspective of the institutional performance of the General Election Supervisory Agency (Bawaslu) in carrying out its supervisory functions. This study aims to analyze the performance of the Tanjungpinang City Bawaslu in conducting oversight during the 2024 Elections. This study employs a descriptive method with a qualitative approach. Research informants were selected using purposive sampling and consisted of leadership and staff members of the Tanjungpinang City Election Supervisory Agency (Bawaslu). Data were collected through interviews and documentation. Data analysis was conducted using the Miles and Huberman interactive model. The performance analysis in this study adopts the perspective on public organization performance proposed by Agus Dwiyanto (2017), which consists of productivity, service quality, responsiveness, responsibility, and accountability. The results of the study indicate that the performance of the Tanjungpinang City Election Supervisory Agency (Bawaslu) is manifested through oversight at all stages, the utilization of organizational resources, the provision of access to oversight information services, and the ability to respond to dynamics and potential vulnerabilities, The performance of duties in accordance with regulations and authority, as well as accountability mechanisms through reporting and documentation of activities. During the 2024 Election period, the Tanjungpinang City Election Supervisory Agency (Bawaslu) did not record any findings or reports of alleged violations that were processed, while its supervisory functions continued to be carried out optimally through various institutional activities in accordance with its duties and authority.